The provenance of export porcelain recovered from the Nan’ao One: a shipwreck in the South China Sea - Zhu, Jian; Li, Naisheng; Henderson, Julian; Glascock, Michael (Cambridge University Press, 2016)
A compositional study employing neutron activation analysis was performed on eleven fragments of Ming dynasty blue-and-white export porcelain recovered from the Nan’ao One shipwreck and 64 samples from three kiln sources. Examination of the compositional data was successful in determining the provenance of the porcelain fragments from the shipwreck. The results indicate that the blue-and-white export porcelain recovered from the Nan’ao One came from two sources: the Jingdezhen and Zhangzhou kilns.